Аналіз адаптації законодавства України з охорони праці до актів Європейського Союзу - Петровська, С. А.; Petrovska, S. A.; Петровський, М. В.; Petrovskyi, M. V. (Право і безпека. – 2023. – № 3 (90). – С. 44-57, 2023)
Проаналізовано стан імплементації норм основних європейських директив, які стосуються забезпечення охорони праці на робочому місці, до українського законодавства. Встановлено, що на початок 2023 року положення проаналізованих директив виконані лише частково, оскільки значна частина положень не імплементовані до українського законодавства з охорони праці. Виявлено чинники, що негативно впливають на процес імплементації. Запропоновано рекомендації для підвищення ефективності та дієвості впровадження актів ЄС у законодавство України. Обґрунтовано прийняття необхідних нормативно-правових актів у сфері охорони праці для гармонізації українського законодавства з європейським. Процес адаптації законодавства України до норм ЄС потребує злагодженої співпраці між усіма гілками влади для ефективної роботи та успішної реалізації їх нормотворчих і правозастосовних повноважень на практиці. Головний акцент поточного процесу наближення законодавства України до законодавства ЄС повинен полягати не в реалізації окремих директив, а у перенесенні загальної архітектури законодавства ЄС з питань охорони здоров’я та безпеки, починаючи з узгодження з Рамковою директивою № 89/391/ЄЕС. Для створення національної державної правової системи, що відповідає нормам ЄС, потрібно одночасно адаптувати наявні закони та ухвалювати нові законодавчі акти, які відповідають європейському правовому полю.

The decision of the European Council dated 23 June 2022 to grant Ukraine the status of an EU candidate became a significant incentive for reforms in the country. Reforming labour protection legislation is one of the most urgent tasks for the successful completion of Ukraine’s European integration and for the development of the country’s economy. The purpose of the article is to study the state of adaptation of Ukrainian legislation in the field of labour protection, in particular, occupational safety and health as well as employees’ health protection, to the legislation of the European Union. To achieve this goal, the general scientific and special scientific methods were used, in particular, dialectical, formal and logical, and comparative legal methods. The state of implementation of the provisions of the main European directives relating to occupational health and safety in the workplace into Ukrainian legislation is analysed. It has been established that by the beginning of 2023, the provisions of the analysed directives have been implemented only partially, since a significant part of the provisions has not been implemented into Ukrainian labour protection legislation. On the basis of the study, there have been identified factors that negatively affect the implementation process. Recommendations for improving the efficiency and effectiveness of the implementation of EU acts into Ukrainian legislation have been proposed. The adoption of the necessary regulatory legal acts in the field of labour protection to harmonise Ukrainian legislation with the European one has been substantiated. The process of Ukrainian legislation adaptation to EU norms requires coordinated cooperation between all branches of government for effective work and successful implementation of their rule-making and law enforcement powers in practice. The main focus of the ongoing process of Ukraine's legislative approximation with the EU should not be on the implementation of individual directives, but on the transfer of the overall architecture of EU legislation on health and safety, starting with the alignment with Framework Directive № 89/391/ЄЕС. In order to create a national state legal system that complies with EU norms, it is necessary to simultaneously adapt existing laws and adopt new legislative acts that comply with the European legal framework.

Проанализировано состояние имплементации норм основных европейских директив, касающихся обеспечения охраны труда на рабочем месте, в украинское законодательство. Установлено, что к началу 2023 года положения проанализированных директив выполнены лишь частично, поскольку значительная часть положений не имплементирована в украинское законодательство по охране труда. Выявлены факторы, негативно влияющие на процесс имплементации. Предложены рекомендации по повышению эффективности и действенности внедрения актов ЕС в законодательство Украины. Обосновано принятие необходимых нормативно правовых актов в сфере охраны труда для гармонизации украинского законодательства с европейским.
Analysis of the Ukrainian legislation on labour protection adaptation to the European Union acts
Keywords: законодавство з охорони праці; безпека та гігієна праці; адаптація українського законодавства; директива; імплементація; labour protection legislation; occupational safety and health; adaptation of Ukrainian legislation; directive; implementation of European standards; законодательство об охране труда; безопасность и гигиена труда; адаптация украинского законодательства; имплементация